Why is rice Amax (at saturating CO2) more heritable than Asat (at ambient CO2)? A commentary on Acevedo‐Siaca et al. (2021). (21st January 2022) - Fabre, Denis; Dingkuhn, Michael
Abstract: Acevedo‐Siaca et al. (2021) reported that A max (at saturating CO2 ) is more heritable than A sat (at ambient CO2 ) in rice and suggested the former to be selected to improve photosynthesis under rising ambient [CO2 ] levels. This commentary hypothesizes sink limitation to be a factor contributing to low genotypic A max via feedback inhibition (acclimation) of photosynthesis as observed under elevated [CO2 ]. This process may to some extent also happen under current ambient [CO2 ]. If confirmed, future breeding for greater photosynthesis should seek improving carbon sink traits as opposed to (or in addition to) modifying the photosynthetic apparatus, which is more difficult.